Pemberdayaan Masyarakat untuk Meningkatkan Optimalisasi Kebersihan Lingkungan serta Potensi UMKM Desa Kalimaro Kecamatan Gebang Kabupaten Cirebon - Solahudin, Ade (Jurnal Pintar Abdimas, 2025)
Kalimaro Village, Gebang District, Cirebon Regency, is an agrarian village with great potential in agriculture, especially corn, but faces obstacles in maintaining environmental cleanliness and maximizing the added value of local products. This Community Service Program aims to empower the people of Kalimaro Village, Gebang District, Cirebon Regency, through optimizing environmental cleanliness and increasing the potential of local MSMEs. The methods used include a participatory approach through socialization, training, and mentoring. This program focuses on increasing awareness of environmental cleanliness, encouraging community participation, and supporting the development of MSMEs by utilizing agricultural products such as corn. Through socialization, training, and mentoring, this program is expected to increase community productivity and improve the economic potential of the village. The conclusion of this study emphasizes that the integration between environmental cleanliness and the development of MSMEs is able to have a positive impact on the health and economy of the village. The implications of this research can be a model of sustainable community empowerment and can be replicated in other villages with similar potential.